Preparation of magnetically doped multilayered functional silica particles via surface modification with organic polymer. (2nd August 2012) - Rahman, M. A.; Miah, M. A. J.; Minami, H.; Ahmad, H.
<x xml:space="preserve">Abstract</x> Magnetically modified functional particles are emerging as one of the most promising candidate in numerous multidisciplinary applications. In this research, a simple process has been developed to prepare magnetically modified aminated silica (SiO2) particles. Herein, submicron‐sized SiO2 particles were modified with poly(methylmethacrylate‐methacrylic acid) by seeded polymerization without any stabilizer. The carboxyl groups localized near the particles surface were then covalently linked with ethylene diamine to prepare aminated composite particles. Iron ions were then precipitated on the surface of aminated composite particles to obtain magnetically doped functional SiO2 particles. The preparation of such particles was confirmed by scanning electron microscopy, Fourier transform infrared, 1H NMR, X‐ray photoelectron spectroscopy and thermogravemetric analyses. Relative measurement of adsorption study of different biomolecules suggested that magnetically doped functional silica particles are comparatively hydrophobic. Copyright © 2012 John Wiley & Sons, Ltd.